Os (des)enredos do amor: a narrativa do fracasso amoroso em contos de Lygia Fagundes Telles - VIANA, Maria José Amaral (Universidade Federal do Pará, 2018)
This study assumes that the love-themed tales from Lygia Fagundes Telles can be read as narratives of love failure. In a poetic and vibrant way, the writer‟s short stories present the search for love and its failure, as weel as delineate man‟s anxieties, tensions and frustrations, which come from the experience of living and relating their feelings to other people. To develop this hypothesis, eight tales were analyzed, being divided into four tracks: love-incommunicability-loneliness, love-estrangement-fragmentation, love-selfishness-blame, love-degradation-death. In our reading, these tracks delineate and interlace the (mis)direction or (un)plots of romantic relationships in Lygia‟s tales and make it possible to analyze the social, ideological, philosophical and psychological values invested and/or virtualized in the narrative fabric, in order to examine and question the representations of love (des)constructed in the fictional universe of the writer.